Forecasting Dhaka stock exchange prices using machine learning models: a Performance analysis - Alam, Md. Iftekharul; Rahman, MD Jubaier; Shakil, Nurul Islam; Ibnat, Maisha; Tasnia, Rifah (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.